Serum homocysteine levels in patients with nonalcoholic fatty liver disease - Stergios A. Polyzos (Annals of Hepatology, 2012)
Background and rational for the study. Nonalcoholic fatty liver disease (NAFLD) is regarded as the hepatic component of insulin resistance (IR) syndrome, but data on serum homocysteine (HCY) are limited. The aim of the study was the evaluation of serum HCY levels in patients with NAFLD.Material and methods. Thirty-one patients (54 ± 11 years, 8 males) with biopsy-proven NAFLD, 15 with simple nonalcoholic fatty liver (NAFL) and 16 with nonalcoholic steatohepatitis (NASH), and 22 healthy controls (52 ± 9 years, 5 males) matched for gender, age and body mass index (BMI), were recruited. Blood samples for HCY, folate, vitamin B12, insulin and standard biochemical tests were obtained after overnight fasting. Homeostatic model of assessment-insulin resistance (HOMA-IR) was calculated.Results. There was no difference in mean serum HCY levels between controls and NAFLD patients (12.6 ± 4.6 vs. 13.5 ± 2.6 mmol/L, respectively; p = 0.432). Serum folate and vitamin B12 were also similar between the study groups. Mean age, BMI, serum folate and vitamin B12 did not differ between NAFL and NASH patients. However, when compared with NAFL patients, NASH patients had lower mean serum HCY levels (12.3 ± 2.5 vs. 14.7 ± 2.1 mmol/L; p = 0.006). HCY was lower by increasing the grading of fibrosis (p = 0.005), portal inflammation (p = 0.029) and steatosis location (p = 0.021). In logistic regression analysis, HCY independently predicted NASH (p = 0.045) after adjustment for gender, age, BMI, AST, glucose and HOMA-IR.Conclusion. Our data suggest that serum HCY levels are lower in NASH compared with NAFL patients and can independently predict NASH. Serum HCY might represent another non-invasive marker for the assessment of NAFLD.